O disclosure de escândalos socioambientais e a reputação corporativa - Oliveira, William Augusto Sousa de (2022)
Voluntary socio-environmental disclosure can be an important factor for more favorable business outcomes, however, when disclosure carries negative information, such as those related to a socio-environmental scandal, they can have a higher tied cost and even impact the organization's reputational image, leading them to adopt mechanisms to neutralize the information. In this sense, the main objective of the study was to investigate the neutralization of disclosure of social and environmental scandals and their relationship with corporate reputation. Furthermore, it is expected that it will contribute to the literature on voluntary dissemination and reputation, as it inserts the literature on neutralization techniques in the relationship between these two theoretical lines, for practice it is expected to contribute to external users in general, with draftsmen and reviewers of voluntary corporate reports to build a more critical view regarding factors that may have disqualified disclosures such as neutralization techniques, and also by presenting neutralization business groupings. For this, an exploratory and quali-quantitative study was carried out, since content analysis was adopted to interpret neutralization on socio-environmental disclosure, as well as statistical tests such as spearman's correlation test, mann-whitney-wilcoxon test, and cluster analysis to verify the relationship between disclosure neutralized and corporate reputation. As results, it was observed the use of neutralization techniques among corporate reports, in addition to distinct neutralization profiles between the social and environmental scenario, also, among the statistical findings there was a positive and moderate correlation between neutralized disclosure and reputation in the year of the scandal and in the following year, as well as an increase in the use of techniques after the negative socio-environmental case. The final considerations of the research point to a less effective use of neutralization in the environmental scenario, and demonstrate how neutralization techniques may not be present among the reputational risk management mechanisms in periods without socio-environmental scandal.